Innate and Adaptive Immune Components in Human Breast Milk and Their Role in Early-Life Immunity - Salsabila, Hanum; Sukmawati, Dewi; Iswanti, Febriana Catur (Biomedical Journal of Indonesia, 2025)
Human breast milk is a uniquely complex biological fluid renowned for delivering essential nutrients to newborns. Beyond its nutritional value, it also contains important immunological components that play a fundamental role in infant health and development. This review explores the immunological characteristics of breast milk, highlighting its diverse array of immune cells and bioactive molecules, including secretory IgA, cytokines, and chemokines. These components actively contribute to the maturation of the infant’s immune system, strengthen defenses against infections, and facilitate the development of a balanced gut microbiome. This discussion also explores how the immune components in breast milk function to benefit infants, examining their protective mechanisms and developmental impacts. Additionally, it addresses how storage conditions—such as freezing, refrigeration, or pasteurization—may alter the integrity and effectiveness of these vital immune factors. Furthermore, the influence of external environmental factors, including maternal diet, stress, and exposure to pollutants, is considered for their potential effects on the immunological quality of breast milk. For this literature review, relevant studies were systematically searched across multiple academic databases, including PubMed, ScienceDirect, Google Scholar, ResearchGate, and Elsevier. The search was limited to publications from the past ten years. Emerging research underscores the adaptive nature of breast milk and its profound impact on early-life immunity, offering valuable insights for optimizing infant feeding practices and potential clinical applications.